Whole genome sequencing of Sars-COV-2 from Covid-19 acquired hemophilia patient - Zainulabid, Ummu Afeera; Periyasamy, Petrick; Kamarudin, Norhidayah; Ibrahim, Ismail; Aslam, Ayesha; Hussain, Mushtaq; Ahmad, Hajar Fauzan (2022)
Acquired hemophilia is an atypical pathology of SARS-CoV-2 infection, which could be variant associated. Here, we share a sequence of SARS-CoV-2 genome from patient with Covid-19 acquired hemophilia. We explore its lineage, genomic and novel structural variations.